Extraction and recovery of bioactive soluble phenolic compounds from brocade orange (Citrus sinensis) peels: Effect of different extraction methods thereon. (1st January 2023) - Wang, Zhirong; Mei, Xiaofei; Chen, Xuhui; Rao, Shnegqi; Ju, Tao; Li, Jiahao; Yang, Zhenquan
Abstract: Brocade orange peels (BOPs), typically treated as discardable residue, contain large amounts of bioactive phenols that can serve as ingredients for value-added products with health-promoting effects. Given this, this study developed a response surface model to optimize the conditions for ultrasound-assisted extraction (UAE). The total phenol and flavonoid contents (TPC, TFC), profiles, and antioxidant activities of peel extracts for free, esterified, and glycosylated-bound phenols (FPs, EBPs, and GBPs) served as metrics for comparing the recoveries using UAE, conventional solvent extraction (CSE), and enzyme-assisted extraction (EAE). The maximum values of practical TPC and TFC achievable under the optimal UAE parameters (17.6 mL/g, 28 min, 26 °C, and 60 W) were 24.07 GAE/DW and 8.34 mg RE/DW, respectively. Extraction methods and especially phenolic fractions were found to exert extremely significant effects on the profiles and bioactivities. For any given phenolic fraction, UAE and particularly EAE were generally superior to CSE in terms of yield and quality of recovered phenolic compounds, as measured according to DPPH and ABTS free radical scavenging capacities. Meanwhile, Observations of predominant levels of polymethoxyflavones in FPs, ferulic acid in EBPs, and hesperetin in GBPs provides a basis for future efforts to obtain specific bioactive phenolic compounds from natural sources. Graphical abstract: Image 1 Highlights: Extract methods and especially phenolic forms affected profiles and bioactivities. UAE and especially EAE gave higher yields of extracts with stronger bioactivities. UAE is a relatively green, economic technique due to its low energy demands. TPC and TFC of various extracts all followed the orders: GBPs ≫ EBPs ≈ FPs. Hesperetin, ferulic acid, and sinensetin were main variables of various extracts.